2009
DOI: 10.1038/sj.bjc.6605472
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour cell detection: a direct comparison between the CellSearch System, the AdnaTest and CK-19/mammaglobin RT–PCR in patients with metastatic breast cancer

Abstract: BACKGROUND: The detection, enumeration and isolation of circulating tumour cells (CTCs) have considerable potential to influence the clinical management of patients with breast cancer. There is, however, substantial variability in the rates of positive samples using existing detection techniques. The lack of standardisation of technology hampers the implementation of CTC measurement in clinical routine practice. METHODS: This study was designed to directly compare three techniques for detecting CTCs in blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 44 publications
5
108
0
8
Order By: Relevance
“…It is well known that the pcr assays show a higher sensitivity compared to the cytofluorometric approach. In fact, a recent paper by Van der Auwera et al (33) showed that in patients with metastatic breast cancer, the ctc positive rate was higher when a qrt-pcr approach for the detection of cK19 and mammoglobin was used compared to other systems like cellsearch or Adnagen, approved ctc detection method. In our population sample, the highest rate of positive samples was observed using the rt-pcr approach (75% positive samples).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the pcr assays show a higher sensitivity compared to the cytofluorometric approach. In fact, a recent paper by Van der Auwera et al (33) showed that in patients with metastatic breast cancer, the ctc positive rate was higher when a qrt-pcr approach for the detection of cK19 and mammoglobin was used compared to other systems like cellsearch or Adnagen, approved ctc detection method. In our population sample, the highest rate of positive samples was observed using the rt-pcr approach (75% positive samples).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify the most effective way to detect ctcs, a few studies compared different enrichment techniques and methods for detection of ctcs in the blood of breast cancer (33,34), prostate cancer (35) and other metastatic carcinoma patients (36,37), sometimes showing concordance in results between methods of analysis or variation in ctc detection rates due to the higher sensitivity of the molecular methodology utilized in the analysis (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…The detection of viable CTCs by a detection of epithelial or tumour specific mRNAs by qRT-PCR is one of the most widely used techniques in the CTC-research field (74)(75)(76)(77)(78). QRT-PCR is the abbreviation for quantitative (real-time) reverse transcription PCR (79), which means that RNA is isolated from the tissue of interest (blood or fraction of a blood sample), is converted to cDNA by a reverse transcriptase reaction, which is then used in a real-time PCR reaction.…”
Section: Ctc Detectionmentioning
confidence: 99%
“…Несмотря на длительную историю изу-чения и совершенствования методологи-ческих подходов [1], вопрос об участии циркулирующих опухолевых клеток (ЦОК) в прогрессировании злокачественного про-цесса остаётся актуальным до настояще-го времени.…”
unclassified